2011
DOI: 10.1182/blood-2010-12-328138
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule Toll-like receptor 7 agonists localize to the MHC class II loading compartment of human plasmacytoid dendritic cells

Abstract: TLR7 and TLR8 are intracellular sensors activated by single-stranded RNA species generated during viral infections. Various synthetic small molecules can also activate TLR7 or TLR8 or both through an unknown mechanism. Notably, direct interaction between small molecules and TLR7 or TLR8 has never been shown. To shed light on how small molecule agonists target TLRs, we labeled 2 imidazoquinolines, resiquimod and imiquimod, and one adenine-based compound, SM360320, IntroductionSince the discovery of type I IFN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 44 publications
(62 reference statements)
3
32
0
3
Order By: Relevance
“…The same structure suggested that a PEG chain might bridge the two identified binding sites in this receptor, one for resiquimod, and the other for RNA, potentially causing a cooperative effect from a bidentate ligand made of RNA and a small molecule derivative of resiquimod. Since RNAs bearing terminal alkyne groups are readily accessible, we synthesized azide derivatives with 1 H -imidazo-[4,5- c ]-purine structure (5254), i.e., derivatives of imidazoquinolines of the quimod series and produced the respective bioconjugates for testing. While the anticipated cooperativity could not be evidenced, we observed that covalent modifications of RNA effectively decrease TLR7-mediated signaling.…”
Section: Introductionmentioning
confidence: 99%
“…The same structure suggested that a PEG chain might bridge the two identified binding sites in this receptor, one for resiquimod, and the other for RNA, potentially causing a cooperative effect from a bidentate ligand made of RNA and a small molecule derivative of resiquimod. Since RNAs bearing terminal alkyne groups are readily accessible, we synthesized azide derivatives with 1 H -imidazo-[4,5- c ]-purine structure (5254), i.e., derivatives of imidazoquinolines of the quimod series and produced the respective bioconjugates for testing. While the anticipated cooperativity could not be evidenced, we observed that covalent modifications of RNA effectively decrease TLR7-mediated signaling.…”
Section: Introductionmentioning
confidence: 99%
“…TLR7/8 recognize single-stranded viral RNA [7, 8]. Upon ligation of the receptor-ligand pair, intracellular signalling is initiated and downstream transcription factors activate genes of proinflammatory cytokines (TNF, IL-1), type I interferons (IFNα) and co-stimulatory molecules (CD80, CD86) [911]. The activation of these genes promotes maturation of dendritic cells (DCs), facilitating the presentation of antigen and stimulation of the ensuing adaptive immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Совсем недавно был поднят вопрос о способах проникновения имиквимода внутрь клетки [1]. Исследования на плазмацитоидных дендритных клетках (для которых TLR7 и TLR8 являются единственными экспрессируемыми молекулами из семейства TLR) показало, что имидазохинолины концентрируются в LAMP1+СD63+HLA-DR+ эндосомах.…”
unclassified
“…У плазмацитоидных ДК эндолизосомальный компартмент специализирован на антигенной презентации через MHC II, поэтому можно сказать, что имиквимод локализуется в MIIC компартменте. Но, так как имиквимод представляет собой слабое основание, способное к пассивной диффузии сквозь клеточную мембрану, в данной работе высказано предположение, что в начале имиквимод пассивно проникает в клетку, после чего аккумулируется в MIIC компартменте, где протонируется и уже не может выйти наружу [1].…”
unclassified